2010
DOI: 10.1016/j.ijrefrig.2010.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Ice slurry applications

Abstract: The role of secondary refrigerants is expected to grow as the focus on the reduction of greenhouse gas emissions increases. The effectiveness of secondary refrigerants can be improved when phase changing media are introduced in place of single phase media. Operating at temperatures below the freezing point of water, ice slurry facilitates several efficiency improvements such as reductions in pumping energy consumption as well as lowering the required temperature difference in heat exchangers due to the benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(59 citation statements)
references
References 13 publications
0
47
0
5
Order By: Relevance
“…The rapid decline in the initial temperature with SI (0.83 °C min -1 ) resulting in a significant reduction of total aerobic bacteria, extend the shelf life, and better control of water content. It was found that the squid stored on SI has significantly higher content of myofibrillar protein (30 mg ml and thus reduces dehydration and oxidation events (V) the complete coverage of the seafood surface Aubourg et al, 2007;Kauffeld et al, 2010).…”
Section: R E G U L a R A R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…The rapid decline in the initial temperature with SI (0.83 °C min -1 ) resulting in a significant reduction of total aerobic bacteria, extend the shelf life, and better control of water content. It was found that the squid stored on SI has significantly higher content of myofibrillar protein (30 mg ml and thus reduces dehydration and oxidation events (V) the complete coverage of the seafood surface Aubourg et al, 2007;Kauffeld et al, 2010).…”
Section: R E G U L a R A R T I C L Ementioning
confidence: 99%
“…Our results could be explained based on a faster cooling rate of slurry ice treatment that leads to a lower temperature, thus, formation of large number of small ice crystals in muscle nuclei, preventing the irreversible destruction of the myofibrils by large ice crystals. More importantly, the concentrations of sodium chloride in the SI is similar to its concentration in marine water, that cause stabilization of the myofibrillar protein fraction implying larger yields during storage, and thus enhancing the quality parameters (Kauffeld et al, 2010). …”
Section: Myofibrillar Protein Analysesmentioning
confidence: 99%
“…An alternative handling procedure called "ike-jime (spiking)" effectively maintains a higher freshness of raw fish by preventing violent motions by the fish itself. This procedure (1) delays the decrease in ATP, Term 2 which is ice was already known [1] [2] and had attracted attention in Japan. However, most icemakers at that time were located at facilities at ports and required 20-24 hours to produce the required amount of ice for a fishing vessel.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to liquid refrigerants, ice slurry shows a two to three times better heat transfer and up to ten times higher energy density for a given temperature change, as a result of which pipe dimensions and pumping power for cold distribution can be reduced. Furthermore, ice slurry is -depending on the additive -an environmentally benign, harmless and non-toxic secondary Extended version of a paper presented at the 11 th IIR Gustav Lorentzen Conference on Natural Refrigerants, Hangzhou, China, 2014 2 refrigerant and is also being used in direct contact cooling of diverse food articles like fish or vegetables (Kauffeld et al, 2010).…”
Section: Introductionmentioning
confidence: 99%